DETERMINAN EFEKTIVITAS PENERAPAN SISTEM AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (SAKIP) - Febiani, Ismi; Irianto, Gugus; Purwanti, Lilik (Jurnal Reviu Akuntansi dan Keuangan)
The purpose of this study is done to determine the level of work units, central governmentsupport, guidance SAKIP evaluation of implementation, and quality and quantity of humanresources of the effectiveness of the implementation of SAKIP. This research is quantitativeresearch, collected by survey through questionnaires. The sample consisted of employees amountedby 110 respondents. This study sampling technique using non-probability sampling with saturated samples (sampling census). The results showed that the working unit commitment andthe quality and quantity of human resources affect the effectiveness of SAKIP, while the centralgovernment support and evaluation guidelines on the implementation SAKIP have no influenceon the effectiveness of SAKIP.Ke ywords: Effectiveness SAKIP Implementation, Government Agencies Performance Accountability System, Employees